The influence of the alveolar ridge shape on the stress distribution in a free-end saddle removable partial denture supported by implant - Martin Júnior, Manoel; Anchieta, Rodolfo Bruniera [UNESP]; Rocha, Eduardo Passos [UNESP]; Pereira, João Antonio [UNESP]; Archangelo, Carlos Marcelo; Freitas Júnior, Amilcar C de [UNESP]; Almeida, Erika Oliveira de [UNESP] (Sociedad Argentina de Investigación Odontológica, 2011)
The alveolar ridge shape plays an important role in predicting the demand on the support tooth and alveolar bone in the removable partial denture (RPD) treatment. However, these data are unclear when the RPD is associated with implants. This study evaluated the influence of the alveolar ridge shape on the stress distribution of a free-end saddle RPD partially supported by implant using 2-dimensioanl finite element analysis (FEA). Four mathematical models (M) of a mandibular hemiarch simulating various alveolar ridge shapes (1-distal desceding, 2- concave, 3-horizontal and 4-distal ascending) were built. Tooth 33 was placed as the abutment. Two RPDs, one supported by tooth and fibromucosa (MB) and other one supported by tooth and implant (MC) were simulated. MA was the control (no RPD). The load (50N) were applied simultaneously on each cusp. Appropriate boundary conditions were assigned on the border of alveolar bone. Ansys 10.0 software was used to calculate the stress fields and the von Mises equivalent stress criteria (σvM) was applied to analyze the results. The distal ascending shape showed the highest σvM for cortical and medullar bone. The alveolar ridge shape had little effect on changing the σvM based on the same prosthesis, mainly around the abutment tooth.

A forma do rebordo alveolar representa um fator importante na previsão da demanda do suporte dentário e do osso alveolar em tratamentos com prótese parcial removível (PPR). Contudo, os dados não são claros quando uma PPR está associada com implantes. Este estudo avaliou a influência da forma sagital do rebordo alveolar na distribuição das tensões de uma PPR de extremidade livre parcialmente suportada por implante usando a aná- lise de elementos finitos (AEF) bidimensional. Foram elaborados quatro modelos (M) matemáticos de um hemiarco mandibular simulando várias formas do rebordo alveolar (1-descendente distal, 2-côncavo, 3-horizontal e 4-ascendente distal). O dente 33 foi considerado como pilar. Duas PPRs, uma suportada por dente e fibromucosa (MB) e outra suportada por dente e implante (MC) foram simuladas. MA foi o modelo controle (sem PPR). Uma carga (50N) foi aplicada simultaneamente em cada cúspide. Condições de contorno adequadas foram assumidas nas margens do osso alveolar. O software Ansys 10.0 foi usado para a análise das tensões segundo o critério das tensões equivalents de von Mises (σvM) para a análise dos resultados. A forma ascendente distal mostrou a maior σvM para osso cortical e medular. A forma do rebordo alveolar teve pouco efeito na alteração da σvM considerando o mesmo tipo de prótese, principalmente em torno do dente pilar.
Influência da forma do rebordo alveolar na distribuição das tensões em prótese parcial removível de extremidade livre suportada por implante
Keywords: Alveolar bone loss; Endosseous dental implantation; Finite element analysis; Periodontal ligament; Perda óssea alveolar; Implante dentário endósseo; Análise de elementos finitos; Ligamento periodontal